FESTIVAL KEBUDAYAAN CANBERRA SEBAGAI ALAT DIPLOMASI PEMERINTAH INDONESIA DI AUSTRALIA (2014-2015) - Setyasih Harini Halifa Haqqi (RESEARCH FAIR UNISRI, 2018)
Culture is regarded as forming international bridges and interactions. With culture, statecan reach influential members of foreign societies who cannot be reached throughtraditional embassy function. Bilateral cooperation between Indonesia and Australia islike a roller coaster or love-hate relationship. This study purpose to explain CanberraFestival as tool of cultural diplomacy of Indonesia in Australia. It is qualitative researchwith literature as source of data. The object is art performance of Indonesia dancerthrough Canberra Festival in Australia. Indonesia has more opportunities make culturaperformance through Canberra Festival after hacking incident. Result of the researchshow culture diplomacy through Canberra Festival can improve relationship betweenIndonesia-Australia after hacking accident. The conclusion is Canberra Festival canincrease tourist from Australia.Key words: foreign relationship, national interest, cultural diplomacy